Towards examining the effectiveness of boxing headguards with thermoplastic polyurethane in mitigating acceleration and risk of head injury using a dynamic head model - Rybak, T. (Lakehead University, 2021)
The sport of boxing historically symbolises a high-risk injury sport due the number of concussions occurring on athletes. Indeed, boxing has shown to have the highest rate of concussions of any individual male sport. Research studies, however, indicate that boxing headgears are generally effective in minimizing concussion risk for training and competitions. Unfortunately, concussions continue to occur even when wearing a protective headguard. As a result, athletes do not always use boxing headguards during training, matches and competitions at the professional level. Based on these concerns, this study examined the capacity of three different types of boxing headguard models to mitigate the risk of concussions by using static and dynamic headguard testing techniques. The researcher included the use of thermoplastic polyurethane (TPU) material inserts in one of the headguard models to observe changes in headguard performance to mitigate concussion risk. The researcher performed static quasi-compression tests to observe changes to the material properties of the headguards, specifically testing percent reduction in the energy absorption, force and deformation of the headguard material. The researcher also performed dynamic tests by mounting the headguard on a surrogate headform and imparting linear and shear impacts to the headform model at different velocities across different headgear locations. The researcher used the dynamic measures of linear and angular accelerations to compute the risk of head injury across the headgear locations. A set of analyses were conducted to examine the capacity of the headguards with and without the TPU material to limit these acceleration measures, and subsequently mitigate the risk of concussion. The results of this study revealed that the TPU material, when implemented into the headguard, had significant effects in mitigating linear accelerations and risk of head injury. This study also found significant interactions between headguard types and impact locations on measures of angular accelerations and risk of head injury, which included measures of Angular Gadd Severity Index and GAMBIT (Generalized Acceleration Model for Brain Injury Threshold) - an index that the combines linear and rotational accelerations. This study is the first to implement TPU material into a boxing headguard and provides strong evidence to mitigate concussion risk in the sport of boxing based on measures of linear and rotational accelerations. In addition, it offers another avenue for manufacturers to improve the capacity of current boxing headgear technologies to better support athletes` safety while practicing in the sport.